2014
DOI: 10.1161/circulationaha.114.010622
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury After Coronary Artery Bypass Grafting and Long-Term Risk of End-Stage Renal Disease

Abstract: Background-Acute kidney injury (AKI) is a common complication after coronary artery bypass grafting (CABG) and is associated with adverse outcomes. However, the relationship between AKI after CABG and the long-term risk of endstage renal disease (ESRD) is unknown. Methods and Results-This study included 29 330 patients who underwent primary isolated CABG in Sweden between2000 and 2008. AKI was classified according to the Acute Kidney Injury Network (AKIN) classification: stage 1, >0.3 mg/dL (>26 μmol/L) or 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 28 publications
5
87
1
2
Order By: Relevance
“…A recently published singlecenter retrospective study conducted in 767 adult critically ill patients, mainly cardiac and postoperative patients, showed that the incidence of AKI was high in this cohort (51.9%) and that the mortality rate increased with progression of the AKI stage [1]. A similar high incidence of AKI and its association with poor outcomes have also been reported in post-CVS patients in several studies [2][3][4][5].…”
supporting
confidence: 71%
“…A recently published singlecenter retrospective study conducted in 767 adult critically ill patients, mainly cardiac and postoperative patients, showed that the incidence of AKI was high in this cohort (51.9%) and that the mortality rate increased with progression of the AKI stage [1]. A similar high incidence of AKI and its association with poor outcomes have also been reported in post-CVS patients in several studies [2][3][4][5].…”
supporting
confidence: 71%
“…A recent multi-center Swedish study of 29,330 post-CABG patients confirmed that the ESRD risk was greater in patients with more severe AKI. The adjusted hazard ratio (95% confidence interval) for ESRD was 2.92 (1.87, 4.55) for AKIN stage 1 and 3.81 (2.14, 6.79) for AKIN stages 2 and 3 [25]. …”
Section: Discussionmentioning
confidence: 99%
“…James et al observed a graded increase in risk of ESRD, which varied by the severity of AKI, among patients who underwent coronary angiography and developed AKI 10. In a nationwide cohort of patients who underwent coronary artery bypass grafting, even a small postoperative increase in serum creatinine was associated with an increase in the long‐term risk of ESRD 11. In this study, Sabe et al tested this possibility by including a time‐varying covariate for coronary revascularization in the model and did not find any significant impact on CKD progression, but this secondary analysis of TREAT cannot completely exclude the possibility that AKI could have contributed to the risk of ESRD in this population 7…”
mentioning
confidence: 99%